Fugitive and codified knowledge: The struggle to control the meaning of environmental hazards - Robert J. Hill (Adult Education Research Conference, 1995)
The purpose of the qualitative research was to determine the ways that knowledge is constructed and used by four Pennsylvania emergent citizens' groups (ECGs) engaged in environmental conflicts, and by the government environmental regulatory agency. It documents the struggle for who controls the meaning of hazardous scenarios. ECGs were cultural producers at the local level, while the state department constructed intellectual and moral capacity from a bureaucratic locus. As such, both were instrumental in community learning, as well as sites of contest. The results show that regulators most frequently constructed "official" knowledge that reproduced the status quo. ECGs constructed "fugitive" knowledge, based on collaborative learning. Bureaucrats did not use local knowledge to make environmental decisions. Citizens responded with rebellious collective action, quiescence and despair.